Science And Religion (Paradigma Al-Qur‘an Untuk Ilmu-ilmu Sosial Menurut Pemikiran Kuntowijoyo) - ANWAR MUDJAHIDIN (Jurnal Dialog, 2017)
This paper aims at analyzing the epistemology of prophetic social science which had proposed by Kuntowijoyo. Sociology as a science cannot decide the direction in which society ought to go, and it makes no recomendations on matter of social policy. Sociology cannot itself deal with problems of good and evil, right and wrong, better and worse, or any others that concern human values. On the other hand religions without any knowledge of social phenomena will not be able to make any changes in the society. Prophetic social science will be able to respond to those dillemas by making the revelation (wahyu) as a source of knowledge. Social sciences do not only produce of statement about what is, but what of value. It can direct where the society ought to changes. According to prophetic social science changes must be directed to humanisation, liberation and trancendency.KATA KUNCI : Ilmu Sosial, al-Qur‘an, Epistemologi